Sigma-1 receptor modulation fine-tunes KV1.5 channels and impacts pulmonary vascular function - Alba Vera-Zambrano; Maria Baena-Nuevo; Susanne Rinné; Marta Villegas-Esguevillas; Bianca Barreira; Gokcen Telli; Angela de Benito-Bueno; José Antonio Blázquez; Belén Climent; Francisco Pérez-Vizcaino; Carmen Valenzuela; Niels Decher; et al. (Elsevier, 2023)
KV1.5 channels are key players in the regulation of vascular tone and atrial excitability and their impairment is associated with cardiovascular diseases including pulmonary arterial hypertension (PAH) and atrial fibrillation (AF). Unfortunately, pharmacological strategies to improve KV1.5 channel function are missing. Herein, we aimed to study whether the chaperone sigma-1 receptor (S1R) is able to regulate these channels and represent a new strategy to enhance their function. By using different electrophysiological and molecular techniques in X. laevis oocytes and HEK293 cells, we demonstrate that S1R physically interacts with KV1.5 channels and regulate their expression and function. S1R induced a bimodal regulation of KV1.5 channel expression/activity, increasing it at low concentrations and decreasing it at high concentrations. Of note, S1R agonists (PRE084 and SKF10047) increased, whereas the S1R antagonist BD1047 decreased, KV1.5 expression and activity. Moreover, PRE084 markedly increased KV1.5 currents in pulmonary artery smooth muscle cells and attenuated vasoconstriction and proliferation in pulmonary arteries. We also show that both KV1.5 channels and S1R, at mRNA and protein levels, are clearly downregulated in samples from PAH and AF patients. Moreover, the expression of both genes showed a positive correlation. Finally, the ability of PRE084 to increase KV1.5 function was preserved under sustained hypoxic conditions, as an in vitro PAH model. Our study provides insight into the key role of S1R in modulating the expression and activity of KV1.5 channels and highlights the potential role of this chaperone as a novel pharmacological target for pathological conditions associated with KV1.5 channel dysfunction.